Konsep Diri dengan Kecemasan Menjelang Masa Bebas pada Narapidana di Rumah Tahanan (Rutan) Kelas IIB Wonogiri, Jawa Tengah - Nugraha, Mas Pinta Ilham (Journal of Psychology and Treatment, 2022)
The purpose of this study was to examine the relationship between self-concept and prisoner anxiety before being released. The sample in this study was 30 prisoners before being released at the Class II B prison in Wonogiri, Central Java using purposive sampling technique. Data were collected using a scale. Data analysis was performed using Product Moment correlation analysis. The results of this study indicate the analysis of the relationship between self-concept variables and anxiety, the correlation coefficient value is -0.758 and the significance value is 0.000 (p < 0.01). The anxiety variable is in the low category, while the self-concept variable is in the high category. The effective contribution of the self-concept variable to anxiety is 46.2%, while the remaining 53.8% is influenced by other variables. The conclusion in this study is that there is a very significant negative relationship between self-concept and prisoners' anxiety before being released.